Teacher training in health care: challenges and possibilities of professorality (Research, Society and Development, 2022)
The object of this text is connected to the context of professional training in health, focusing on the health teacher. The objective is to understand the health professorality, based on the challenges and possibilities pointed out by scientific literature. This is a qualitative research, following the assumptions of the Integrative Literature Review. The research for the studies was conducted in the Virtual Health Library and in the CAPES (Coordination for the Improvement of Higher Education Personnel) Portal of Journals, applying Thematic Content Analysis to those selected. This text takes charge of the category "health area teacher training: challenges and possibilities", originated from the analysis of 31 articles included in the review. It was possible to understand that teachers in the health area must have knowledge and experience in the specific area and also a strong pedagogical formation. The role of graduate studies in the training of health area teachers points out the gaps present in these formative spaces for higher education teaching. In addition, HEIs (Higher Education Institutions) should be responsible for teacher training, since they enable the exchange of experiences among teachers. It is concluded that it is important to understand the challenges and possibilities that permeate professorality in the health area in order to improve this field of action.